2023
DOI: 10.3389/fvets.2023.1183689
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for atrial fibrillation in dogs with dilated cardiomyopathy

Abstract: IntroductionAtrial fibrillation secondary to dilated cardiomyopathy (DCM) frequently affects large-breed dogs. The aim of the present study was to identify risk factors for the development of atrial fibrillation in dogs of different breeds with an echocardiographic diagnosis of DCM.MethodsIn this multicenter retrospective study, we searched the electronic databases of five cardiology referral centers for dogs with an echocardiographic diagnosis of DCM. A comparison of clinical and echocardiographic variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(19 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Notably, cardiovascular disorders, in particular valvular disease, exhibit relevance across both species. However, other factors integral to human AF, such as health behaviors (e.g., smoking tobacco and alcohol intake) and broader health factors (e.g., height, concurrent non-cardiac disorders), are either not applicable or have been inadequately investigated in the canine population [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, cardiovascular disorders, in particular valvular disease, exhibit relevance across both species. However, other factors integral to human AF, such as health behaviors (e.g., smoking tobacco and alcohol intake) and broader health factors (e.g., height, concurrent non-cardiac disorders), are either not applicable or have been inadequately investigated in the canine population [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, recognized risk factors for incident AF include genetics, advanced age, male sex, and Caucasian ethnicity [ 11 ]. In dogs, many studies have reported a higher prevalence of AF in large-breed animals [ 1 , 5 , 6 , 9 , 10 , 11 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Notably, a high heritability estimate for AF, with a likely dominant mode of inheritance, has been demonstrated specifically in Irish Wolfhounds [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations